2003
DOI: 10.1038/sj.cgt.7700628
|View full text |Cite
|
Sign up to set email alerts
|

Combined suicide gene therapy for pancreatic peritoneal carcinomatosis using BGTC liposomes

Abstract: Peritoneal dissemination is a common end-stage complication of pancreatic cancer for which novel therapeutic modalities are actively investigated, as there is no current effective therapy. Thus, we evaluated, in a mouse model of pancreatic peritoneal carcinomatosis, the therapeutic potential of a novel nonviral gene therapy approach consisting of bis-guanidinium-tren-cholesterol (BGTC)-mediated lipofection of a combined suicide gene system. Human BxPC-3 pancreatic cells secreting the carcinoembryonic antigen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The latter approach is also known as gene-directed enzyme prodrug therapy (GDEPT) and is basically a two-step process. First, the enzymecoding gene is selectively delivered to tumors followed by the systemic or intratumoral administration of a prodrug in a subtherapeutic dose [8,9]. The accumulation of the prodrug's toxic metabolites then causes target-specific death in the enzyme-bearing cells or the surrounding cells ( Figure 6.1).…”
Section: Introductionmentioning
confidence: 99%
“…The latter approach is also known as gene-directed enzyme prodrug therapy (GDEPT) and is basically a two-step process. First, the enzymecoding gene is selectively delivered to tumors followed by the systemic or intratumoral administration of a prodrug in a subtherapeutic dose [8,9]. The accumulation of the prodrug's toxic metabolites then causes target-specific death in the enzyme-bearing cells or the surrounding cells ( Figure 6.1).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] However, the efficacy of gene therapy, designed to correct inherited or acquired genetic defects and/or confer new genetic and phenotypic characteristics to cells, 3,4,7 is limited in the treatment of PC. 3,4,[8][9][10][11][12][13][14] Immunotoxins, bacteria or plant-derived protein toxins vehicled by molecules bind target antigens or receptors to the cell surface, 5,6,[15][16][17] the most widely used products being diphtheria toxin (DT) and pseudomonas exotoxin, which arrest cytosolic protein synthesis by modifying the elongation factor 2.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Currently, some studies have reported that commercially available transfection reagents (i.e., Lipoplexes) have proved useful for nonviral gene therapy. [31][32][33][34][35] We too are very interested in these reagents. Nevertheless, we expect that targeted gene therapy by sonoporation using contrast agents for HCC would be a much easier method, based on our experience using contrast agents to detect hepatic tumors by US examination in clinical situations.…”
Section: Discussionmentioning
confidence: 99%